Firm Actions to Develop an Ambidextrous Sales Force. (February 2020) - Panagopoulos, Nikolaos G.; Rapp, Adam; Pimentel, Michael A.
While research on employee ambidexterity is growing, there is little investigation on what firms can do to enhance their competitiveness in this space. Leveraging a human resource lens, we advance a comprehensive model depicting three firm-level ambidexterities as key performance drivers that can help firms achieve bottom-line outcomes. Specifically, we focus on (1) ambidexterity in skill-enhancing practices (i.e., selection, training), which ensure employees have relevant service-sales knowledge, skills, and abilities; (2) ambidexterity in motivation-enhancing practices (i.e., metrics, incentives), which help motivate employees to perform service-sales activities; and (3) ambidexterity in opportunity-enhancing practices (i.e., data, tools use), which enable employees to perform service-sales activities. Our findings suggest that ambidextrous firms—or those that balance service- and sales-related elements when implementing their systems and processes—enjoy greater sales force and firm financial performance. Finally, we test boundary conditions for these relationships and find that competitive intensity enhances the positive effects of all ambidexterity constructs. We conclude with implications for theory and practice.